Iron Oxides 2016
DOI: 10.1002/9783527691395.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Measurements and Characterization

Abstract: IntroductionWhen characterizing the magnetic properties of iron oxides, whether they be geological or synthetic, there are four main factors that are of interest: (i) composition of the iron oxides; (ii) concentration in a bulk material; (iii) particle size distribution; and (iv) magnetic interaction between particles. These four factors are important because they govern the magnetic behavior that affects the usefulness of an iron oxide in any specific application. For example, composition can provide informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For example, it has been shown that superparamagnetic behavior and high magnetic moment are desirable for both MRI and MPI [ 5 , 6 , 7 ]. The magnetic properties of a material will depend upon the particles’ chemical composition, size, shape and whether there is any magnetic interaction amongst the particles [ 3 , 8 ]. Chemical composition will determine to a large extent the saturation magnetization of a material.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that superparamagnetic behavior and high magnetic moment are desirable for both MRI and MPI [ 5 , 6 , 7 ]. The magnetic properties of a material will depend upon the particles’ chemical composition, size, shape and whether there is any magnetic interaction amongst the particles [ 3 , 8 ]. Chemical composition will determine to a large extent the saturation magnetization of a material.…”
Section: Introductionmentioning
confidence: 99%
“…There is a broad palette of magnetic methods that help in identifying the composition, concentration and the effective particle size of ferromagnetic minerals [2]. Table 1 summarizes the information that some of these methods can provide.…”
Section: Methodsmentioning
confidence: 99%
“…In many applications, it is important to understand the way in which a magnetic particle responds to an external field. Composition, particle size, and degree of particle interaction all play a role in determining the efficiency of delivery, and usage; therefore, these properties need to be controlled in the synthesis of materials [2].…”
Section: Introductionmentioning
confidence: 99%